Achieving stable implosion through hydro-equivalent analysis for direct-driven inertial confinement fusion - Z. Li; X.H. Yang; G.B. Zhang; B. Zeng; B.H. Xu; Z.H. Chen; Y.Y. Ma; F.Q. Shao; J. Zhang (Nuclear Fusion)
The control of Rayleigh–Taylor instability (RTI) in target implosion compression is a classical problem in laser-driven inertial confinement fusion (ICF). Modeling the evolution of RTI by using high-dimensional radiation hydrodynamics simulations requires significant computational resources. In this paper, we present a novel approach to evaluate and predict the growth of RTI in direct-driven ICF. The target implosion velocities and accelerations at critical moments are derived according to the laser profiles and the target structures by the hydro-equivalent analysis and spherical ablation theory, combined with the adiabat from the one-dimensional simulation. Then, combining with the nonlinear RTI theory, the RT spikes penetration ratio is used to evaluate the integrity of the target. The most stable laser profile and target structure design can be quickly selected and the development of RTI is verified in the two-dimensional radiation hydrodynamics simulation. The results show that the areal density is increased by 68.2% by applying the most stable laser profile and target structure design compared with that of the initial case. These findings have significant implications for enhancing direct-drive ICF instability control.